Microparticles and nanoparticles-based approaches to improve oral treatment of Helicobacter pylori infection - Paes Dutra, Jessyca Aparecida [UNESP]; Gonçalves Carvalho, Suzana [UNESP]; Soares de Oliveira, Aline [UNESP]; Borges Monteiro, Jéssica Raquel; Rodrigues Pereira de Oliveira Borlot, Jéssica; Tavares Luiz, Marcela [UNESP]; Bauab, Tais Maria [UNESP]; Rezende Kitagawa, Rodrigo; Chorilli, Marlus [UNESP] (Taylor & Francis, 2024)
Helicobacter pylori is a gram-negative, spiral-shaped, flagellated bacterium that colonizes the stomach of half the world’s population. Helicobacter pylori infection causes pathologies of varying severity. Standard oral therapy fails in 15–20% since the barriers of the oral route decrease the bioavailability of antibiotics and the intrinsic factors of bacteria increase the rates of resistance. Nanoparticles and microparticles are promising strategies for drug delivery into the gastric mucosa and targeting H. pylori. The variety of building blocks creates systems with distinct colloidal, surface, and biological properties. These features improve drug-pathogen interactions, eliminate drug depletion and overuse, and enable the association of multiple actives combating H. pylori on several fronts. Nanoparticles and microparticles are successfully used to overcome the barriers of the oral route, physicochemical inconveniences, and lack of selectivity of current therapy. They have proven efficient in employing promising anti-H. pylori compounds whose limitation is oral route instability, such as some antibiotics and natural products. However, the current challenge is the applicability of these strategies in clinical practice. For this reason, strategies employing a rational design are necessary, including in the development of nano- and microsystems for the oral route.
Keywords: drug delivery nanosystems; H. pylori; microcarriers; nanocarriers; natural products; oral antibiotics